2013
DOI: 10.1016/j.bcp.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

7-Ketocholesterol induces P-glycoprotein through PI3K/mTOR signaling in hepatoma cells

Abstract: 7-Ketocholesterol (7-KC) is found at an elevated level in patients with cancer and chronic liver disease. The up-regulation of an efflux pump, P-glycoprotein (P-gp) leads to drug resistance. To elucidate the effect of 7-KC on P-gp, P-gp function and expression were investigated in hepatoma cell lines Huh-7 and HepG2 and in primary hepatocyte-derived HuS-E/2 cells. At a subtoxic concentration, 48-h exposure to 7-KC reduced the intracellular accumulation and cytotoxicity of P-gp substrate doxorubicin in hepatoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 43 publications
(59 reference statements)
1
42
0
1
Order By: Relevance
“…39), which is encoded by MDR1 . Arceci and colleagues reported that rapamycin can reverse the MDR phenotype in human T-cell lymphoblastic leukemia cell lines (47), and increased activation of the PI3K/mTOR pathway was recently associated with overexpression of MDR1 in HCC (48). However, the effect of mTORC2 inhibition on MDR1 expression remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…39), which is encoded by MDR1 . Arceci and colleagues reported that rapamycin can reverse the MDR phenotype in human T-cell lymphoblastic leukemia cell lines (47), and increased activation of the PI3K/mTOR pathway was recently associated with overexpression of MDR1 in HCC (48). However, the effect of mTORC2 inhibition on MDR1 expression remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, schweinfurthin G treatment‐promoted mislocalization of mTOR reduces the interaction between mTOR and its activator, RheB (Bao et al, ). In hepatocellular carcinoma cells, activity of the drug resistance export protein P‐glycoprotein (Pgp) can be induced by the oxysterol 7‐ketocholesterol in an mTOR dependent manner (Wang et al, ). However, schweinfurthin treatment reduces the activity of Pgp suggesting a potential nexus between schweinfurthin treatment, cholesterol homeostasis, and oxysterol signaling through mTOR (Sheehy et al, ).…”
Section: Mechanismmentioning
confidence: 99%
“…However, for troleandomycin, HuH-7 cells yielded a 2-fold lower k inact and 70-fold higher K I value compared to human recombinant CYP3A4 inhibition assay. A higher K I value in HuH-7 cells could be attributable to slow diffusion into the cells or active removal from the cells by export pumps (Wang et al 2013, Zhang et al 2012). A comparison between HuH-7 cells and human recombinant CYP3A4 demonstrated a potential use for DMSO-treated HuH-7 cell line as a whole cell system for measuring CYP3A4 inhibition.…”
Section: Discussionmentioning
confidence: 99%